Systemutformning av autonom batteridriven traktor inom lantbruket - Ericson, Martin (SLU/Dept. of Energy and Technology, 2018)
In this study, data from different studies were used to find how much energy that a conventional tractor required per hectare when it was performing different operations on a field. Data for operation speed and power demand were taken from an earlier study for each task of the tractor model Valtra 6600. In this report, the operation speed for each task on the field were simulated in Excel together with a given electrical motor, a battery and a charger. This was done in order to find what affected the working time for an autonomous battery powered tractor. Two scenarios were studied in Excel; how the distance to the charger, and different charging speeds affected the working hours in order to operate a 200-hectare farm.